Espaço agrário e assalariamento no Nordeste: das características gerais ao estudo particular das condições de trabalho e saúde dos abacaxizeiros da Paraíba - Torres, Éricson da Nóbrega (2020)
The advance of capital over agriculture in the Northeast has provided countless changes in the socio-spatial dynamics of the region, whose expression in the territories is revealed in changes that alter the organization of the agrarian space with repercussions on the geographical dynamics of work. These transformations, driven by the mobility of capital in the countryside, bring a great challenge to a critical geographic reading of the space that allows us to understand the complexities/contradictions of capitalist relations of production in northeastern agriculture and its repercussions on labor relations in the countryside. The aim of the work is to analyze the evolution, spatialization and characteristics of salaried work in northeastern agriculture between 1996 and 2006, with the state of Paraíba as the central focus of observation and as a case study the salaried work in pineapple activity. Emphasis was placed on workers' living, working and health conditions. The central hypothesis that guides this research is the advance of capital over the northeastern/from Paraiba agrarian space promoted the expansion of rural wage labor and that this work relationship, besides being heterogeneous, is distributed differently according to the size of agricultural establishments, the spatial subunits, sex, age and type of agricultural activity, in addition to being subjected to a strong process of exploitation and precariousness that has profound repercussions on the conditions of life and health of workers. As a methodological path, we worked with the literature review, the survey and processing of secondary data and fieldwork. This comprised: a) interviews with small and large pineapple producers; with employers' representatives; rural workers' unions; with municipal agriculture secretaries and with representatives of the Ministry of Labor; b) the application of 90 questionnaires to salaried workers in the pineapple activity in order to analyze their living, working and health conditions. It was found that at the height of the capitalist expansion in the countryside, that is, between 1970-1980, there was in fact a great expansion of wage labor, however, afterwards what was proven was the retreat of the same if we take into account the last four decades , although, the focus of the period studied in this work (1995-2006), there was a slight advance. However, the tendency of wage labor in the northeastern and paraiban fields was towards retraction, particularly in large production units, possibly due to the substitution effect, it grows in units of family production. Regarding female and child wage labor, both have been drastically reduced. The first, because companies demand a labor force that has more physical strength to guarantee higher rates of profit; and the second motivated by the complaints and inspections of competent agencies that fight child labor. Finally, what gives homogeneity to every category of rural wage earner is the exploitation to which workers are subjected under the predominance of the expansionist, uncontrollable and devastating capitalist mode of production and the nature, conditions of life, work and health of the rural population.